1995
DOI: 10.1039/ft9959103281
|View full text |Cite
|
Sign up to set email alerts
|

Reversible interaction of NH3 with the framework of template-free zeolite-type SAPO-34

Abstract: The interaction of ammonia with the template-free SAPO-34 framework is studied by XRD, 29Si, 27AI and 31P magic angle spinning (MAS) NMR and IR spectroscopy and temperature-programmed desorption (TPD). A reversible loss of crystallinity upon NH, adsorption-desorption at room temperature is accompanied by the reversible formation of new 27AI and 31 P NMR spectroscopic peaks, and the displacement of the chemical shifts of 29Si, 27AI and 31P nuclei. Rupture of some AI-0-P bonds is proposed. Upon NH, desorption, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
15
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 16 publications
3
15
0
Order By: Relevance
“…They showed that NH 3 -TPD is a good method to determine the Brønsted acidity of SAPO-34. 20 This fact encouraged us to measure the NH 3 -TPD spectra of SAPO-34 with particle sizes of less than B3 mm. The relationship between the mole fraction of Si (the value of z) and the amount of NH 3 desorption is shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…They showed that NH 3 -TPD is a good method to determine the Brønsted acidity of SAPO-34. 20 This fact encouraged us to measure the NH 3 -TPD spectra of SAPO-34 with particle sizes of less than B3 mm. The relationship between the mole fraction of Si (the value of z) and the amount of NH 3 desorption is shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Two peaks at 3625 and 3598 cm À1 can be attributed to two types of Si(OH)Al groups differed in their localization. The bridged group with y = 3598 cm À1 is assumed to be localized in the hexagonal prism, forming an H-bond with adjacent oxygen atoms of the framework while the isolated bridged OH groups pointing towards the center of the elliptical cages give the vibration frequency at 3625 cm À1 [15][16][17][18]. These two types of OH groups have been considered to have similar acidic properties and to be the active sites for acid-catalyzing reaction [19,20].…”
Section: Resultsmentioning
confidence: 99%
“…Such cleavage of the bonding metalwoxygen upon sorption of a strong base molecule has been found for cloverite24 and for aluminophosphate molecular sieves. 27 The observations with sorbed pyridine fully support the model.…”
Section: Sorption Of Strong Basesmentioning
confidence: 53%